The Slugs of Florida (Gastropoda: Pulmonata) - Lionel A. Stange (EDIS)
This document is EENY-087 (originally published as DPI Entomology Circular No. 197), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999. Revised: August 2002.